Linear quadratic regulator design for wheelchair control using monte-carlo simulation method - Uǧur, Efgan; Kara, Tolgay; Abdulhafez, Abdulhafez (Institute of Electrical and Electronics Engineers Inc., 2023)
In this paper, we present Monte-Carlo simulation for a linearized wheelchair model that use Linear Quadratic Controller. The controller has two weighting matrices which are Q and R. These weighting matrices are important to select optimal gain matrix value. Trial and Error method has been usually used in Linear Quadratic Controller because of simplicity but very difficult to choose the best values that have good control performances. Without giving up the simplicity of the Trial and Error method, we propose Monte-Carlo method. So, many closed loop simulations using Monte-Carlo method, optimal gain matrix value is calculated. Effectiveness of the both method is discussed comparatively. The results indicate that the Monte-Carlo method are more powerful to select optimal gain matrix and better performance for the stability of the system. © 2023 IEEE.
Keywords: Engineering controlled terms; Engineering uncontrolled terms; Engineering main heading